2005
DOI: 10.1007/s00441-005-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal developmental expression of the PDZ scaffolds Na+-H+ exchanger regulatory factors 1 and 2 in the rat cochlea

Abstract: Sensory transduction in the mammalian cochlea requires the maintenance of specialized fluid compartments with distinct ionic compositions. This is achieved by the concerted action of diverse ion channels and transporters, some of which can interact with the PDZ scaffolds, Na + -H + exchanger regulatory factors 1 and 2 (NHERF-1, NHERF-2). Here, we report that NHERF-1 and NHERF-2 are widely expressed in the rat cochlea, and that their expression is developmentally regulated. Reverse transcription/polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 64 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…The specificities of the NHERF1 and NHERF2 antibodies for their targets in immunocytochemistry have been demonstrated previously (Kanjhan et al, 2006). We also tested the specificity of the NHERF1 and NHERF2 antibodies on immunoblots of electrophorectically separated SDS-solubilized brain lysate.…”
Section: Nherf1 and Nherf2 Expression In Brain Lysatesmentioning
confidence: 80%
See 3 more Smart Citations
“…The specificities of the NHERF1 and NHERF2 antibodies for their targets in immunocytochemistry have been demonstrated previously (Kanjhan et al, 2006). We also tested the specificity of the NHERF1 and NHERF2 antibodies on immunoblots of electrophorectically separated SDS-solubilized brain lysate.…”
Section: Nherf1 and Nherf2 Expression In Brain Lysatesmentioning
confidence: 80%
“…We have recently reported that NHERF1/2 are widely distributed in the cochlea. In particular, NHERF2 immunolabeling was also evident in walls of large blood vessels including spiral modiolar artery and vein (Kanjhan et al, 2006). While the precise function(s) of NHERF2 within endothelial cells remains to be determined, it is interesting to note that several members of the previously characterized NHERF2 binding partners, namely P2Y1 receptor (Fam et al, 2005), PTH receptor (Mahon et al, 2002), and β 2 AR (Hall et al, 1998) are also expressed in endothelial cells of the mammalian brain.…”
Section: Distribution Of Nherf1 and Nherf2 Proteins In The Rat Brainmentioning
confidence: 93%
See 2 more Smart Citations
“…l Extensive TASK-1-IR in glial cells and their processes ensheated at the walls of small to medium-sized blood vessels located deep inside the brain parenchyma in the medullary median septum. Abbreviations: inferior cerebellar peduncle (icp), spinal trigeminal tract (Sp5) c procedures were modified from our previous studies (Kanjhan et al 2004a(Kanjhan et al , 2006. After intracardiac perfusion with heparinized 0.9% NaCl solution containing 1.45 mM NaNO 2 , the brains were fixed in situ with 4% paraformaldehyde in 0.1 M phosphate buffer (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%